Transition metal doped CeO2 for photocatalytic removal of 2-chlorophenol in the exposure of indoor white light and antifungal activity - M. Tariq Qamar; Shahid Iqbal; M. Aslam; Ahmad Alhujaily; Anum Bilal; Komal Rizwan; Hafiz Muhammad Umer Farooq; Tahir Ali Sheikh; Ali Bahadur; Nasser S. Awwad; Hala A. Ibrahium; Hala A. Ibrahium; et al. (Frontiers in Chemistry, 2023)
Besides natural sunlight and expensive artificial lights, economical indoor white light can play a significant role in activating a catalyst for photocatalytic removal of organic toxins from contaminated water. In the current effort, CeO2 has been modified with Ni, Cu, and Fe through doping methodology to study the removal of 2-chlorophenol (2-CP) in the illumination of 70 W indoor LED white light. The absence of additional diffractions due to the dopants and few changes such as reduction in peaks’ height, minor peak shift at 2θ (28.525°) and peaks’ broadening in XRD patterns of modified CeO2 verifies the successful doping of CeO2. The solid-state absorption spectra revealed higher absorbance of Cu-doped CeO2 whereas a lower absorption response was observed for Ni-doped CeO2. An interesting observation regarding the lowering of indirect bandgap energy of Fe-doped CeO2 (∼2.7 eV) and an increase in Ni-doped CeO2 (∼3.0 eV) in comparison to pristine CeO2 (∼2.9 eV) was noticed. The process of e-– h+ recombination in the synthesized photocatalysts was also investigated through photoluminescence spectroscopy. The photocatalytic studies revealed the greater photocatalytic activity of Fe-doped CeO2 with a higher rate (∼3.9 × 10−3 min-1) among all other materials. Moreover, kinetic studies also revealed the validation of the Langmuir-Hinshelwood kinetic model (R2 = 0.9839) while removing 2-CP in the exposure of indoor light with a Fe-doped CeO2 photocatalyst. The XPS analysis revealed the existence of Fe3+, Cu2+ and Ni2+ core levels in doped CeO2. Using the agar well-diffusion method, the antifungal activity was assessed against the fungus M. fructicola and F. oxysporum. Compared to CeO2, Ni-doped CeO2, and Cu-doped CeO2 nanoparticles, the Fe-doped CeO2 nanoparticles have outstanding antifungal properties.